Ligand-induced endocytosis and nuclear localization of angiotensin II receptors expressed in CHO cells - A.J. Merjan; C.A. Kanashiro; J.E. Krieger; S.W. Han; A.C.M. Paiva (Brazilian Journal of Medical and Biological Research, 2001)
A construct (AT1R-NF) containing a "Flag" sequence added to the N-terminus of the rat AT1 receptor was stably expressed in Chinese hamster ovary cells and quantified in the cell membrane by confocal microscopy after reaction with a fluorescein-labeled anti-Flag monoclonal antibody. Angiotensin II bound to AT1R-NF and induced endocytosis with a half-time of 2 min. After 60-90 min, fluorescence accumulated around the cell nucleus, suggesting migration of the ligand-receptor complex to the nuclear membrane. Angiotensin antagonists also induced endocytosis, suggesting that a common step in the transduction signal mechanism occurring after ligand binding may be responsible for the ligand-receptor complex internalization.